Outcome Measures Used in Clinical Trials for Behcet Syndrome: A Systematic Review - DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2014)
Behcet syndrome (BS) is a multisystem vasculitis that is most active during young adulthood, causing serious disability and significant impairment in quality of life. Differences in the disease course, severity, and organ involvement between patients, depending on the age at presentation and sex, makes it impossible to determine a single management strategy. The diversity and variability in the outcome measures used in clinical trials in BS makes it difficult to compare the results or inform physicians about the best management strategy for individual patients. There is a large unmet need to determine or develop validated outcome measures for use in clinical trials in BS that are acceptable to researchers and regulatory agencies. We conducted a systematic review to describe the outcomes and outcome measures that have been used in clinical trials in BS. This review revealed the diversity and variability. in the outcomes and outcome measures and the lack of standard definitions for most outcomes and rarity of validated outcome tools for disease assessment in BS. This systematic literature review will identify domains and candidate instruments for use in a Delphi exercise, the next step in the development of a core set of outcome measures that are properly validated and widely accepted by the collaboration of researchers from many different regions of the world and from different specialties, including rheumatology, ophthalmology, dermatology, gastroenterology, and neurology.
Keywords: BEHCET SYNDROME; OUTCOMES; ASSESSMENT; SYSTEMATIC REVIEW; QUALITY-OF-LIFE; DAGGER-ETS DISEASE; DOUBLE-BLIND TRIAL; RECURRENT APHTHOUS STOMATITIS; LONG-TERM PROGNOSIS; INTERFERON-ALPHA TREATMENT; CROSS-CULTURAL ADAPTATION; DOSE CYCLOSPORINE-A; ORAL ULCER ACTIVITY; C-REACTIVE PROTEIN